1989
DOI: 10.1021/ja00197a004
|View full text |Cite
|
Sign up to set email alerts
|

Solvent dynamical effects in electron transfer: evaluation of electronic matrix coupling elements for metallocene self-exchange reactions

Abstract: The functional dependence of the rate constants for self-exchange, kex, for a series of metallocene redox couples to solvent-induced variations in the nuclear frequency factor, vn, engendered by alterations in the longitudinal solvent relaxation time, tl, are utilized to deduce values of the electronic matrix coupling element, Hn, for electron exchange. The analysis exploits the sensitivity of the kex-rL"' dependence to the degree of reaction adiabaticity and hence Hn for a given electron-exchange reaction. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 0 publications
5
78
1
Order By: Relevance
“…Given that the LR approximation is noticeably less valid for the 5 A anion than for the cation reactant ( Figure 7, vide supra), the free energy-reaction coordinates should be decidedly nonparabolic, so that disparate AM values might be expected for these systems. It is worth noting that the effective diameters of the majority of ET reactants commonly utilized to probe solvent dynamical effects are somewhat larger than 5 A; for example, a = 7-8 A for simple metallocenes [9][10][11].…”
Section: (Ae) and Ae(o) --(Ae)mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the LR approximation is noticeably less valid for the 5 A anion than for the cation reactant ( Figure 7, vide supra), the free energy-reaction coordinates should be decidedly nonparabolic, so that disparate AM values might be expected for these systems. It is worth noting that the effective diameters of the majority of ET reactants commonly utilized to probe solvent dynamical effects are somewhat larger than 5 A; for example, a = 7-8 A for simple metallocenes [9][10][11].…”
Section: (Ae) and Ae(o) --(Ae)mentioning
confidence: 99%
“…Barrier-crossing frequencies that are markedly 2 accelerated above TL- 1 have been observed for a number of outer-sphere ET reactions in primary alcohols [9][10][11][12][13][14][15][16]. Part of the often large (-10 fold) rate accelerations can be accounted for[15J in terms of a continuum-based formulation due to Hynes [17].…”
mentioning
confidence: 99%
“…An example of this approach, involving self exchanges of metallocenium-metallocene (Cp2M + 1") redox couples in various polar Debye solvents is worth highlighting here since ET rate-solvent dependencies are observed that span the limits of nonadiabatic and adiabatic behavior [12]. For ferrocenium-ferrocene couples, the rate constants k'ex (corrected for AG*-solvent variations) are almost independent of the solvent dynamics, as discerned by tL• 1 .…”
Section: Dtic 7tabmentioning
confidence: 95%
“…Interestingly, substantial (up to ca 50 fold) variations in .L are observed in such media, from ca. 0.25 to 10 ps [12]. Since analytic theories predict commonly that vn,-T -1, correspondingly large variations in Vn are anticipated to be achieved by suitable alterations in -5-the solvent medium.…”
Section: Dtic 7tabmentioning
confidence: 99%
“…3B). The similar electrode potential of ferrocyanide and ferrocenemethanol (less than 10 mV apart), thermoneutral character, and rapid electron self-exchange rate constants allow desirable electron transfer and thus make this pair of reactants suitable for a chemically amplified electrochemical detection scheme [18][19][20][21].…”
Section: Chemical Amplification Of Ferrocenemethamentioning
confidence: 99%